The Kynurenine Pathway of Tryptophan Degradation is Activated During Osteoblastogenesis. (18th December 2014) - Vidal, Christopher; Li, Wei; Santner-Nanan, Brigitte; Lim, Chai K.; Guillemin, Gilles J.; Ball, Helen J.; Hunt, Nicholas H.; Nanan, Ralph; Duque, Gustavo
Abstract: The mechanisms involved in the anabolic effect of interferon gamma (IFNγ) on bone have not been carefully examined. Using microarray expression analysis, we found that IFNγ upregulates a set of genes associated with a tryptophan degradation pathway, known as the kynurenine pathway, in osteogenic differentiating human mesenchymal stem cells (hMSC). We, therefore, hypothesized that activation of the kynurenine pathway plays a role in osteoblastogenesis even in the absence of IFNγ. Initially, we observed a strong increase in tryptophan degradation during osteoblastogenesis with and without IFNγ in the media. We next blocked indoleamine 2, 3-dioxygenase-1 (IDO1), the most important enzyme in the kynurenine pathway, using a siRNA and pharmacological approach and observed a strong inhibition of osteoblastogenesis with a concomitant decrease in osteogenic factors. We next examined the bone phenotype of Ido1 knockout ( Ido1 −/− ) mice. Compared to their wild-type littermates, Ido1 −/− mice exhibited osteopenia associated with low osteoblast and high osteoclast numbers. Finally, we tested whether the end products of the kynurenine pathway have an osteogenic effect on hMSC. We identified that picolinic acid had a strong and dose-dependent osteogenic effect in vitro. In summary, we demonstrate that the activation of the kynurenine pathway plays an important role during the commitment of hMSC into the osteoblast lineage in vitro, and that this process can be accelerated by exogenous addition of IFNγ. In addition, we found that mice lacking IDO1 activity are osteopenic. These data therefore support a new role for the kynurenine pathway and picolinic acid as essential regulators of osteoblastogenesis and as potential new targets of bone-forming cells in vivo. Stem Cells 2015;33:111–121